A BOOK REVIEW OF BASIC SPEAKING: WHATSAPP-BASED DAILY CONVERSATION - Nufus, Siti Hayatun; Sanhas, Tasman (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The rapid growth of digital technology has significantly changed how English is taught and learned in today’s classrooms. In the field of English as a Foreign Language (EFL), teachers increasingly use mobile-assisted language learning (MALL) to create learning environments that are more communicative, flexible, and accessible. One of the most popular tools for this purpose is WhatsApp, a mobile messaging platform that supports real-time, authentic, and collaborative communication (Kukulska-Hulme, 2020). The book, titled Basic Speaking: WhatsApp-Based Daily Conversation (2020), was written by Dr. Maulina, Prof. Dr. Nurdin Noni, and Prof. Drs. Muhammad Basri, and published by Deepublish. It contains approximately 103 pages of material designed for one semester of university-level speaking instruction. The textbook provides a practical model that integrates Communicative Language Teaching (CLT) with Mobile-Assisted Language Learning (MALL), reflecting the increasing role of mobile technology in education. In this context, the book Basic Speaking: WhatsApp-Based Daily Conversation by Maulina, Noni, and Basri (2020) offers an innovative approach to teaching speaking. It combines the principles of communicative language teaching with the practicality of digital collaboration. The book was written in response to the growing need to modernize English materials for university students in Indonesia, where digital literacy and social media play an important part in students’ everyday lives. It is designed for basic speaking courses and aims to bridge classroom learning with students’ mobile communication habits. By doing so, it allows learners to practice conversational English through WhatsApp both inside and outside the classroom (Alshammari, 2020). One of the main problems in many EFL settings is limited exposure to authentic communication. The book addresses this challenge by using familiar technology as a way for students to stay engaged with English beyond class time. This review provides an academic evaluation of the book’s content, teaching design, and its relevance to English language teaching. It outlines the book’s main features, discusses its strengths and weaknesses, and examines how it integrates both linguistic and socio-cultural competence. The review ends with several recommendations for teachers and researchers who are interested in developing similar digital-based speaking materials.